Impression Management Strategies Used by Foreign Students - Ulyhelyi, Mária; Barizsné Hadházi, Edit (International Journal of Engineering and Management Sciences, 2018)
In this paper, we examined a general human behaviour, the impression management among university students. People are interested in how others think about them. At the organizational level, they can also benefit from being positively judged by others. Effort to create this positive image is Impression Management, which has several measurement options. In this paper, we conducted research on the impressions strategies used by first year international students of University of Debrecen, Faculty of Economics and Business Administration, Bachelor in Business Administration and Management programme. In our analysis we used the questionnaire consisting of 22 questions developed by Bolino and Turnley. We analysed what strategies are typical for the examined student group and to what extent? Are there differences in the strategies employed by men and women and depending on their cultural background.